Lycopodiaceae in Brazil. Conspectus of the family II. The genera Lycopodiella, Palhinhaea, and Pseudolycopodiella - Øllgaard, Benjamin; Windisch, Paulo G. (Rodriguésia, 2016)
Abstract This paper treats the Brazilian species of three genera of the Lycopodiaceae: Lycopodiella with four species (one endemic), Palhinhaea with six (two endemics), and Pseudolycopodiella with seven (one endemic). The species are described, and keys and illustrations, or references to illustrations for their identification are provided. The nomenclature is reviewed. Representative specimens are cited, and the general distribution and habitats are indicated. Pseudolycopodiella squamata is described as new to science. Resumo Este trabalho trata as espécies de três gêneros de Lycopodiaceae: Lycopodiella com quatro espécies (uma endêmica), Palhinhaea com seis (duas endêmicas) e Pseudolycopodiella com sete (uma endêmica). As espécies são descritas, sendo apresentadas chaves e ilustrações ou referências a ilustrações para sua identificação. A nomenclatura está revisada, espécimes representativos são citados, a distribuição geral e habitats são indicados. Pseudolycopodiella squamata é descrita como nova para a ciência.